The most commonly injured nerves at surgery: A comprehensive review. Issue 2 (12th November 2020) - Sharp, Elizabeth; Roberts, Melissa; Żurada‐Zielińska, Agnieszka; Zurada, Anna; Gielecki, Jerzy; Tubbs, Richard Shane; Loukas, Marios
Abstract: Iatrogenic nerve injury during surgery is a major source of concern for both patients and surgeons. This study aimed to identify the nerves most commonly injured during surgery, along with the commonly associated operative procedures. A literature search was conducted using the PubMed database to identify nerves commonly injured during surgery, along with the surgical procedure associated with the injury. The following 11 nerves, ranked in order with their associated surgical procedures, were found to be the most commonly injured: (a) intercostobrachial nerve in axillary lymph node dissections and transaxillary breast augmentations, (b) vestibulocochlear nerve in cerebellopontine tumor resections and vestibular schwannoma removals, c) facial nerve in surgeries of the inner ear and cheek region, (d) long thoracic nerve in axillary lymph node dissections, (e) spinal accessory nerve in surgeries of the posterior triangle of the neck and cervical lymph node biopsies, (f) recurrent laryngeal nerve in thyroid surgeries, (g) genitofemoral nerve in inguinal hernia and varicocele surgeries, (h) sciatic nerve in acetabular fracture repairs and osteotomies, (i) median nerve in carpal tunnel release surgeries, (j) common fibular nerve in varicose vein and short saphenous vein surgeries, and (k) ulnar nerve in supracondylar fracture surgeries. Although the root cause of iatrogenic nerve injury differs for each nerve, there are four unifying factors that could potentially decrease this risk for all peripheral nerves. These four influencing factors include knowledge of potential anatomical variations, visual identification of at‐risk nerves during the procedure, intraoperative nerve monitoring, and expertise of the surgeon.